2022
DOI: 10.14814/phy2.15216
|View full text |Cite
|
Sign up to set email alerts
|

To identify normovolemia in humans: The stroke volume response to passive leg raising vs. head‐down tilt

Abstract: Volume responsiveness can be evaluated by tilting maneuvers such as head-down tilt (HDT) and passive leg raising (PLR), but the two procedures use different references (HDT the supine position; PLR the semi-recumbent position). We tested whether the two procedures identify "normovolemia" by evaluating the stroke volume (SV) and cardiac output (CO) responses and whether the peripheral perfusion index (PPI) derived from pulse oximetry provides similar information.In randomized order, 10 healthy men were exposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 92 publications
0
4
1
Order By: Relevance
“…At both visits, participants underwent PLR. In this study, no differences in ∆SV were observed [22]. The total water deficit after 6-8 h of fasting was about 500 mL [23,24].…”
Section: Discussioncontrasting
confidence: 51%
See 3 more Smart Citations
“…At both visits, participants underwent PLR. In this study, no differences in ∆SV were observed [22]. The total water deficit after 6-8 h of fasting was about 500 mL [23,24].…”
Section: Discussioncontrasting
confidence: 51%
“…Of course, the presence of increased intra-abdominal pressure must also be considered. Studies in healthy subjects comparing a 6 h fasting with a normal breakfast showed no difference in SV during PLR [22].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In this study, a built‐in automatic, accurate algorithm for detecting artifacts (missed, extra, and misaligned beat detections) as well as ectopic beats was applied. This feature was not used in the studies by McHugh, nor the recent publication by Sejersen et al (2022) probably explaining the lack of significant results. Notably, the road from registration of the electrical activity of the heart to the presentations of an ECG and final results of the FFT passes several stations in digital signal analysis in the shape of electrical components, analog‐to‐digital conversion, filtering, and analytical algorithms.…”
Section: Discussionmentioning
confidence: 99%